An investigation into the implementation of risk based internal auditing: case study of the National Railways of Zimbabwe - Mapfumo, Raymond (Midlands State University, 2017)
This study sought to analyze the implementation of risk based internal auditing by organizations in Zimbabwe, with particular reference to the National Railways of Zimbabwe. In this study the knowledge and opinions of NRZ managers and internal auditors was sought to establish how risk based internal auditing was being implemented. Attention was to be drawn on discovering whether the implementation was carried out correctly and if not, then make corrective recommendations. The research commenced with defining the problem in chapter one, discovering how the implementation should have been carried out through reviews of literature in chapter two, laying out in chapter three the research methods to be employed to get data, obtaining data through interviews and questionnaires and analyzing findings in chapter four, through to reaching conclusions and making recommendations in chapter five. The findings of the study were that the organization was not benefitting fully from implementation of risk based internal auditing because of weaknesses in its enterprise risk management systems. It was therefore recommended that effective implementation of risk based internal auditing required management to establish an effective risk management framework.